Predictive Roles of Three-Dimensional Psychological Pain, Psychache, and Depression in Suicidal Ideation among Chinese College Students - Li, Huanhuan; Fu, Rong; Zou, Yingmin; Cui, Yanyan (Frontiers in Psychology, 2017)
The aim of the present research was to explore the predictive roles of 3 screening measures in the evaluation of preexisting suicide risk factors in a sample of undergraduate students. We assessed 1061 students using the Beck depression and suicidal ideation scales(BDI-I) (BSI), the Psychache Scale (PAS), and the three-dimensional Psychological Pain Scale (TDPPS). Simultaneous multivariate regression analysis showed that the predictive values of pain avoidance scores and BDI scores for suicidal ideation were more significant than that of the PAS scores. Subsequently, 42 patients with major depressive disorder (MDD), 39 students with subthreshold depression(SD) , and 18 healthy controls were voluntarily recruited. Students with SD were divided into high suicidal ideation (HSI-SD) and low suicidal ideation (LSI-SD) groups. Pain avoidance scores differed significantly among the MDD, HSI-SD, LSI-SD and healthy control groups, whereas the difference in BDI scores was marginally significant. Pain avoidance and BSI scores were significantly higher in the MDD and HSI-SD groups than those in the LSI-SD and healthy control groups. However, no significant difference was observed in BDI scores between the HSI-SD and LSI-SD groups. Pain avoidance and depression, rather than psychache, may be promising predictors of suicidal ideation in a Chinese young adult population.